Energy Literacy Profile of Vocational High School Teacher Candidates for Renewable Energy Engineering Expertise Program - Iis Rahmania Putri; Agus Setiawan; Dindin Nasrudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
This study examines the energy literacy profile of engineering students as vocational high school teacher candidates for renewable energy engineering expertise programs in terms of 3 energy literacy domains: knowledge, attitudes, and behavior. This research uses a quantitative approach with a descriptive-comparative design, conducted on 135 engineering students from 3 study programs at the Indonesian University of Education. The results obtained are that the energy literacy knowledge of engineering students as vocational high school teacher candidates for renewable energy engineering expertise programs is low. Still, their energy literacy attitudes and behaviors are quite good. There was no statistically significant difference in energy literacy between the female and male student groups. In this study, it was known that students from 3 study programs received energy content from different courses. Their energy literacy results were influenced by differences in the range and depth of energy content provided by each study program. The results of this study can be a consideration for universities to develop energy literacy education and learning models and pay attention to the needs, content, and depth of energy content in each study program, especially study programs that are qualified as teachers candidates of vocational high school Renewable Energy Engineering Expertise Program.